Complete Resolution of a Large Bicuspid Aortic Valve Thrombus with Anticoagulation in Primary Antiphospholipid Syndrome - Rachwan, Rayan Jo; Daher, Ghassan E.; Fares, Jawad; Rachoin, Rachoin (Frontiers in Cardiovascular Medicine, 2017)
Native aortic valve thrombosis in primary antiphospholipid syndrome (APLS) is a rare entity. We describe a 38-year-old male who presented with neurological symptoms and a cardiac murmur. Transthoracic echocardiography detected a large bicuspid aortic valve thrombus. Laboratory evaluation showed the presence of antiphospholipid antibodies. Anticoagulation was started, and serial echocardiographic studies showed complete resolution of the aortic valve vegetation after 4 months. The patient improved clinically and had no residual symptoms. This report and review of the literature suggests that vegetations in APLS can be treated successfully with conservative treatment, regardless of their size.